Sociodemography Factors and Selection Method of Contraception for Postpartum in Public Health Center “Socah”, Bangkalan - Esyuananik Esyuananik; Uswatun Khasanah; Anis Nur Laili (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
The World Health Organization recommend setting a minimum pregnancy distance of 24 months from previous deliveries in order to reduce the risk of maternal and child mortality and illness. The postpartum period is one of the opportunities for a mother to understand and use effective contraception. The contraceptive needs of a postpartum mother will be fulfilled properly through the provision of counseling using a variety of methods, overcoming cost barriers and providing permanent and long-term contraceptive methods at various health facilities. So that every postpartum mother will get a contraceptive method according to their needs and choices. This research used cross-sectional design. Population was all mother after childbirth in the work area of Public Health Center “Socah”, Bangkalan in June-August 2017. Sample size was 48, selected by accidental sampling. The independent variable were sociodemography (education and culture), meanwhile the dependent variable was selecting postpartum contraception methods. The data used primary data using a questionnaire on the postpartum. Prior to grab data respondents had given counseling on a variety of contraceptive methods, then follow to choose one of the contraceptives currently labor. Sociodemography questionnaire used in the study was a questionnaire that has been proven validity and reliability. Data were analyzed by Chi-Square test. The results showed that there was a significant influence in the selection of contraceptive methods based on sociodemography, they are education and culture. Need to provide information for each prospective acceptor by using decision-making instruments so that all prospective acceptors can choose contraceptives that are understood and in accordance with their health conditions. Keywords: Education, Culture, Contraseption selection